2017
DOI: 10.1155/2017/5039702
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Pricing Strategy Based on the Stability of Smart Grid for Green Internet of Things

Abstract: The ever increasing demand of energy efficiency and the strong awareness of environment have led to the enhanced interests in green Internet of things (IoTs). How to efficiently deliver power, especially, with the smart grid based on the stability of network becomes a challenge for green IoTs. Therefore, in this paper we present a novel real-time pricing strategy based on the network stability in the green IoTs enabled smart grid. Firstly, the outage is analyzed by considering the imbalance of power supply and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…The use of the internet is conceptually comparable to these disciplines, given that they provide heightened sensations and are addictive in nature (Curry, Wagner, & Grothaus, 1991 Thombs & Osborn, 2019). However, we observed that past IS studies, regardless of the context and certainly not in green-IT (Chen, Hui, Su, Fang, & Hui, 2017;Shuja et al, 2017), rarely employed both awareness and financial disincentives together. Studies suggest that the simultaneous employment of both awareness and financial disincentives (like pricing) could lead to substantial attitudinal changes, compared to using only one of them (Haque, Ahmend, & Rahman, 2013;Shuja et al, 2017;Verdonk-Kleinjan, Candel, Knibbe, Willemsen, & de Vries, 2011).…”
Section: Australasian Journal Of Information Systemsmentioning
confidence: 68%
“…The use of the internet is conceptually comparable to these disciplines, given that they provide heightened sensations and are addictive in nature (Curry, Wagner, & Grothaus, 1991 Thombs & Osborn, 2019). However, we observed that past IS studies, regardless of the context and certainly not in green-IT (Chen, Hui, Su, Fang, & Hui, 2017;Shuja et al, 2017), rarely employed both awareness and financial disincentives together. Studies suggest that the simultaneous employment of both awareness and financial disincentives (like pricing) could lead to substantial attitudinal changes, compared to using only one of them (Haque, Ahmend, & Rahman, 2013;Shuja et al, 2017;Verdonk-Kleinjan, Candel, Knibbe, Willemsen, & de Vries, 2011).…”
Section: Australasian Journal Of Information Systemsmentioning
confidence: 68%
“…For instance, topological analysis for the optimal power flow was conducted, with the association between devices determined by power grid (e.g., the minimum power lost on power lines) [23]. A real-time pricing strategy was also proposed for SG based on the green IoT [27], which concentrated on the physical layer modeling, assuming the cyber layer to be optimally designed. On the other hand, although HSCNs have been popularized in 5G cellular networks to support large scale CPSs, characteristics of users/devices in the physical layer were mostly neglected [15], [28].…”
Section: Related Workmentioning
confidence: 99%